Impact of the Training on the Compliance and Persistence of Weekly Bisphosphonate Treatment in Postmenopausal Osteoporosis: A Randomized Controlled Study - AKYÜZ, GÜLSEREN DERYA (IVYSPRING INT PUBL, 2013)
Long-term patient adherence to osteoporosis treatment is poor despite proven efficacy. In this study, we aimed to assess the impact of active patient training on treatment compliance and persistence in patients with postmenopausal osteoporosis. In the present national, multicenter, randomized controlled study, postmenopausal osteoporosis patients (45-75 years) who were on weekly bisphosphonate treatment were randomized to active training (AT) and passive training (PT) groups and followed-up by 4 visits after the initial visit at 3 months interval during 12 months of the treatment. Both groups received a bisphosphonate usage guide and osteoporosis training booklets. Additionally, AT group received four phone calls (at 2nd, 5th, 8th, and 11th months) and participated to four interactive social/training meetings held in groups of 10 patients (at 3rd, 6th, 9th, and 12th months). The primary evaluation criteria were self-reported persistence and compliance to the treatment and the secondary evaluation criteria was quality life of the patients assessed by 41-item Quality of Life European Foundation for Osteoporosis (QUALEFFO-41) questionnaire.. Of 448 patients (mean age 62.4 +/- 7.7 years), 226 were randomized to AT group and 222 were randomized to PT group. Among the study visits, the most common reason for not receiving treatment regularly was forgetfulness (54.9% for visit 2, 44.3% for visit 3, 51.6% for visit 4, and 43.8% for visit 5), the majority of the patients always used their drugs regularly on recommended days and dosages (63.8% for visit 2, 60.9% for visit 3, 72.1% for visit 4, and 70.8% for visit 5), and most of the patients were highly satisfied with the treatment (63.4% for visit 2, 68.9% for visit 3, 72.4% for visit 4, and 65.2% for visit 5) and wanted to continue to the treatment (96.5% for visit 2, 96.5% for visit 3, 96.9% for visit 4, and 94.4% for visit 5). QUALEFFO scores of the patients in visit 1 significantly improved in visit 5 (37.7 +/- 25.4 vs. 34.0 +/- 14.6, p<0.001); however, the difference was not significant between AT and PT groups both in visit 1 and visit 5. In conclusion, in addition to active training, passive training provided at the 1st visit did not improve the persistence and compliance of the patients for bisphosphonate treatment.
Keywords: Bisphosphonates; osteoporosis; patient education; medication adherence; OF-LIFE QUESTIONNAIRE; VERTEBRAL FRACTURES; RISEDRONATE TREATMENT; EUROPEAN FOUNDATION; ADHERENCE; WOMEN; ALENDRONATE; RISK; MORTALITY; THERAPY